The Picture of Dorian Gray and the character construction on screen - Maria Vitoria Matos Santos; Carlos Augusto Viana da Silva (Entrelaces - Revista do Programa de Pós-Graduação em Letras-UFC, 2024)
This paper is an analysis of the construction of Dorian Gray, from the novel The Picture of Dorian Gray (2004), by Oscar Wilde, making a parallel with the same character from the TV show Penny Dreadful (2014-2016), by John Logan. After briefly explaining the main points of Aestheticism, we will focus on the construction of some narrative events that occur in Dorian Gray’s life, as well as to the observation of its representation on the television screen, seeking to understand some changes. As theoretical background, we use authors who deal with themes of literature and adaptation, such as Robert Stam (2006), Décio Torres Cruz (2014), Deborah Cartmell and Imelda Whelehan (2010). We start from the point that Penny Dreadful is a literary collage, and that particular traits of construction of both characters emphasize their differences, creating new motivations for the narrative development in the process of adaptation from the book to television.KeywordsDorian Gray. Oscar Wilde. Penny Dreadful.